2012
DOI: 10.1108/09534811211213937
|View full text |Cite
|
Sign up to set email alerts
|

Persuasive brand management

Abstract: Purpose -The purpose of this paper is to build a conceptual framework that enables an improved comprehension of how brand meaning is constructed. Design/methodology/approach -Conceptual implications are drawn from an analysis and discussion of the literature in the fields of brand management, meanings, rhetoric, and narratives. Findings -Brand managers are progressively losing control over the multiple sources of brand meaning. Brand meaning is co-created during the consumer-brand relationship and the customer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 38 publications
(58 reference statements)
0
50
0
Order By: Relevance
“…All the constructs were measured using multi-item scales adapted from the previous studies (Table 1). The scales had been earlier tested and used for their robustness in similar studies (Brakus et al, 2009; Iglesias and Bonet, 2012; Jung & Soo, 2012). Hence, it is suggested that the scale is appropriate for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…All the constructs were measured using multi-item scales adapted from the previous studies (Table 1). The scales had been earlier tested and used for their robustness in similar studies (Brakus et al, 2009; Iglesias and Bonet, 2012; Jung & Soo, 2012). Hence, it is suggested that the scale is appropriate for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…As such, in an increasingly global, dynamic and consumer-driven marketplace, companies are recognizing the need to relinquish some control of their brands and increase their level of engagement with consumers at different levels (Grönroos & Voima, 2013; Hatch & Schultz, 2010; Iglesias, Ind, & Alfaro, 2013; Ind, Iglesias, & Markovic, 2013; Kennedy & Guzmán, 2016; Schultz, 2016). As consumer power has augmented due to an increase of available information, and proliferation and higher levels of adoption of technological platforms, consumer engagement in the market has also increased (Asmussen, Harridge-March, Occhiocupo, & Farqhuar, 2013; Baldus, Voorhees, & Calantone, 2015; Harmeling, Moffett, Arnold, & Carlson, 2017; Iglesias & Bonet, 2012; Malthouse, Haenlein, Skiera, Wege, & Zhang, 2013; Vallaster & von Wallpach, 2013).…”
mentioning
confidence: 99%
“…Understanding how specifically the distributer-producer relationship works in the wine market will improve the competitiveness of distributors and wine producers. We emphasize the importance of this study in the managers' capability to interpret and create meanings with significance for the partners, to influence customer expectations and build strong relations with them beyond the traditional customer satisfaction (Iglesias & Bonet, 2012;Kotler, 2000).…”
Section: Discussionmentioning
confidence: 98%